Collaborative Security Mechanism in Detecting Intrusion Activity - Abdollah, M. F.; Mas'ud, M. Z.; Sahib, S.; Selamat, S. R.; Yusof, R. (2010)
The rapidly increasing array of Internet-scale threats is a pressing problem for every organization that utilizes the network. Organizations often have limited knowledge as well as capability to detect and respond to these threats. The sharing of information related to probes and attacks is a facet of an emerging trend toward ‘’collaborative security’’. Collaborative security mechanism provide network administrator with a valuable tool in this increasingly hostile environment. This research paper proposed a new Collaborative Security Model which incorporated existing mechanism such as prevention by using firewall or any network devices, detection by using Intrusion Detection System (IDS), response by correlating any log files gathered from multiple devices and forensic which tracing the activity of the intrusion. The model integrates and compensates the advantages and disadvantages of each mechanism in order to create a strong defensive model for the network infrastructure.